Data Privacy and Trust in Cloud Computing Building trust in the cloud through assurance and accountability - Lynn, Theo; Mooney, John G.; van der Werff, Lisa; Fox, Grace (Palgrave Studies in Digital Business & Enabling Technologies,, 2021)
This open access book brings together perspectives from multiple disciplines including psychology, law, IS, and computer science on data privacy and trust in the cloud. Cloud technology has fueled rapid, dramatic technological change, enabling a level of connectivity that has never been seen before in human history. However, this brave new world comes with problems. Several high-profile cases over the last few years have demonstrated cloud computing's uneasy relationship with data security and trust. The volume explores the numerous technological, process and regulatory solutions presented in academic literature as mechanisms for building trust in the cloud, including GDPR in Europe, as well as examining the - limited - evidence for their success. The massive acceleration of digital adoption resulting from the COVID-19 pandemic is introducing new and significant security and privacy threats and concerns. Against this backdrop, this book provides a timely reference and organising framework for considering how we will assure privacy and build trust in such a hyper-connected digitally dependent world. This book presents a framework for assurance and accountability in the cloud and reviews the literature on trust, data privacy and protection, and ethics in cloud computing. Theo Lynn is Full Professor of Digital Business at DCU Business School, Ireland. John G. Mooney is Associate Professor of Information Systems and Technology Management at the Pepperdine Graziadio Business School, United States. Lisa van der Werff is Associate Professor of Organisational Psychology at DCU Business School, Ireland. Grace Fox is Assistant Professor of Digital Business at DCU Business School, Ireland.